The Power of Celebrity Endorsement in Brand Choice Behavior: An Empirical Study of Consumer Attitudes in Jordan - Sami Alsmadi (Journal of Accounting, Business and Management (JABM), 2006)
The main purpose of this study is to explore consumer attitudes towards the role of celebrity endorsement in television advertising in Jordan, and provide guidance to advertising makers and specialists to improve the effectiveness of celebrity-based television advertising. The study was based on an empirical research approach, which used a convenience sample of 450 students, drawn from Yarmouk University campus. The data was analyzed by various statistical techniques, such as Frequency analysis, Descriptive analysis, One Sample t-Test, and One-Way ANOVA. The main findings showed that Jordanian respondents were generally interested in celebrity endorsement in advertising, as the majority recognized its overall attractiveness, though did not find it convincing enough in terms of brand choice behavior. The study suggested to reconsider the way celebrities were projected in advertising, or even chosen, within the context of the Jordanian culture. The study urged further research to explore this issue in greater depth in Jordan. The study made several other recommendations in the light of the findings